АЛГОРИТМ ПРИСКОРЕНОГО МОДУЛЯРНОГО ПРИМНОЖЕННЯ ЧИСІЛ ВЕЛИКОГО РОЗРЯДНОСТІ ПРИ ФІКСОВАНОМУ МОДУЛІ - Samofalov , K. G.; Saliba Sunna, Ramzi Anwar; Romanovsky, A. E. (Problems of Informatization and Control, 2005)
A new algorithm for the software implementation of modular multiplication is proposed, using pre-computations with a constant modulus. The developed modular multiplication algorithm provides greater performance compared to the known algorithms focused on the variable value of the modulus, especially when implemented in software on low-bit microcontrollers and smart cards. In this case, the proposed algorithm provides approximately twice the performance compared to Montgomery’s algorithm with a relatively small amount of additional memory.